Reversal of H-bonding direction by N-sulfonation in a synthetic reverse-turn peptide motif - Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Thorat, Shridhar H.; Gonnade, Rajesh G.; Nair, Roshna V.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2015)
This communication depicts an intriguing example of hydrogen-bonding reversal upon introduction of a sulfonamide linkage at the N-terminus of a synthetic reverse-turn peptide motif. The ready availability of two sulfonyl oxygen atoms, as hydrogen-bonding acceptors, combined with the inherent twisted conformation of sulfonamides are seen to act as switches that engage/disengage the hydrogen-bond at the sticky ends/termini.

Role of N-terminal proline in stabilizing the Ant-Pro zipper motif - Kheria, Sanjeev; Nair, Roshna V.; Kotmale, Amol S.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (New Journal of Chemistry, 2015)
Hetero-chiral hybrid peptides of the general sequence (L)alpha beta(D)(n)alpha beta(n) featuring proline (Pro, a constrained alpha-amino acid) and anthranilic acid (Ant, a constrained beta-amino acid) as building blocks, where n = 2, 4 etc., form a three-dimensional zipper-like architecture. These zipper peptides attain stable conformation by balancing the co-operative contribution of two competing non-covalent forces, namely hydrogen bonding and aromatic stacking. However, the selection of the N-terminal residue also stands to be one of the key contributors in stabilising the unusually long-range intramolecular hydrogen bond, featuring 26 atoms in the H-bonded ring observed at the termini. This article deals with the substitution alterations at the N-terminus of the zipper motif and their consequent influences on its structure and stability. In this study, the N-terminal Pro residue of the zipper motif was substituted with a flexible amino acid, alanine, and a constrained acyclic amino acid, 2-aminoisobutyric acid, to investigate the role of N-terminal proline in stabilizing the Ant-Pro zipper motif, and its stabilities were assessed by employing solution-state NMR and restrained MD simulation studies.

Residue dependent hydrogen-bonding preferences in orthanilic acid-based short peptide beta-turn motifs - Jedhe, Ganesh S.; Vijayadas, Kuruppanthara N.; Kotmale, Amol S.; Sangtani, Ekta; Shinde, Dinesh R.; Gonnade, Rajesh G.; Rajamohanan, Pattuparambil R.; Sanjayan, Gangadhar J. (RSC Advances, 2016)
This communication describes the competition between native beta-turn (C10) and 2-aminobenzenesulfonic acid (SAnt)( orthanilic acid)-based pseudo beta-turn (C11) in their hybrid peptides. Solid-state crystal structure and solution-state NMR studies revealed that C10 and C11 can be simultaneously observed under appropriate conditions. The variable temperature NMR coefficient data suggest that the isolated C11/C14 hydrogen bond is weaker in comparison with the consecutive C10 and C11 turns.